10 The association between paraoxonase (PON1) polymorphisms and cardiovascular injuries among nanoworkers. (11th October 2013) - Liou, S; Chung, Y; Liao, H; Lin, M; Lin, C; Li, W; Wang, C; Wu, W
Abstract : Objectives: The market of nanomaterials products is rapidly expanding. The lack of scientific evidence describing accompanying exposure and cardiovascular health risks regarding its guidance and regulation. The objectives of this study was to examine (1) the association between different nanomaterials exposure and cardiovascular biomarkers and (2) effect of PON1 Q192R genetic polymorphism on cardiovascular biomarkers among nanoworkers. Methods: In this cross-sectional study, we recruited 258 workers exposed to nanomaterials and 200 non-exposed controls from 14 nanomaterial handling plants in Taiwan from 2009 to 2011. The non-exposed controls were selected from the same plants, but they did not handle nanomaterials. We used the control banding matrix to categorize the risk level of nanoworkers. For each participant, we collected blood specimens to measure cardiovascular biomarkers and genotyping of PON1 (Q192R) . In addition, heart rate variability (HRV) was tested. Results: PON1 Q192R genetic polymorphism associated with PON1 activity and HRV (SDNN, RMSSD, and TP). We also found that different nanomaterials exposure affected particular cardiovascular biomarkers by controlling PON1 Q192R genetic polymorphism. Such as nano-carbon tube exposure resulted in a decrease in fibrinogen. Nano-SiO2, nano-TiO2 and nano-Ag exposure separately resulted in an increase in fibrinogen, VCT and RMSSD. Conclusion: This study adopted comprehensive cardiovascular examinations to establish the association between different nanomaterials exposure and cardiovascular injuries. We also found possible causal associations that NPs may activate the autonomic nervous system and result in alterations of heart rate variability. Additionally, PON1 Q192R genetic polymorphisms were significant variables for PON1 activity and HRV.